Управување со квалитетот во одбраната на Република Македонија со „Шест сигма“- методологија - Ивановски, Стефан (Економски факултет, УКИМ, Скопје, 2015)
Although historically, the army has always beenа synonym for discipline and organization, and numerous initiatives for managing organizations have their origin in the army, in recent years, the business sector, particularly the manufacturing industry, provides the benchmark for quality. Six sigma represents one of the most sophisticated and latest methodologies for quality management. Six Sigma takes the best practices from multiple methodologies, philosophies and statistical tools and with the proper implementation brings the organization in a state of excellence and continuous improvement. Therefore, more and more organizations in the public sector start to implement this methodology in order to bring the quality of work to the highest degree. The defense departments of the Western countries (US, UK, Netherlands, etc.) are one of the first public institutions that began to implement this methodology for total quality management. They have achieved huge savings in material and human resourses, and also increased the effectiveness, efficiency and satisfaction of the end customer - the soldier who carries out combat mission. Six Sigma is a methodology which is divided into five steps: define, measure, analyze, improve and control. In each of these steps, six sigma uses a range of tools for management and statistical tools for quality control. With proper and well planned implementation, Six Sigma achieves perfection, both in the execution of certain projects and in transforming the organization to organization based on quality and continuous improvement. The purpose of this paper is to introduce the Six Sigma methodology for quality management to the defence sector in the Republic of Macedonia and through empirical research and comparative analyzes to perceive the possibility of its implementation in the Ministry of Defence of the Republic of Macedonia.
Quality management in Macedonian ministry of defence through “Six sigma” methodology
Докторска дисертација одбранета во 2015 година на Економскиот факултет во Скопје, под менторство на проф. д–р Бобек Шуклев.
Keywords: quality, six sigma, methodology, army, organizations, defence, public sector